Semiconducting silicon–phosphorus frameworks for caging exotic polycations. Issue 55 (17th June 2022) - Yox, Philip; Porter, Andrew P.; Dorn, Rick W.; Kyveryga, Victoria; Rossini, Aaron J.; Kovnir, Kirill
Abstract : Silicon phosphides with a new structure have been synthesized. These salt inclusion materials contain exotic polycations such as [Ba6 Cl] 11+ . The structure and properties are investigated. Abstract : A series of novel semiconductors AAe6 Si12 P20 X (A = Na, K, Rb, Cs; Ae = Sr, Ba; X = Cl, Br, I) is reported. Their crystal structures feature a tetrahedral Si–P framework with large zeolite-like pores hosting two types of cations, monoatomic A + and unprecedented octahedral X@Ae6 11+ . Mixing of the A and Ba cations was detected by single crystal X-ray diffraction and confirmed by multinuclear solid state NMR. The reported compounds are highly stable semiconductors with a bandgap range from 1.4 to 2.0 eV.